Patience and Steadfast Faith in Addressing Marital Conflict: A Thematic Study of Qur'anic Verses on Life Trials - Farhan Indra; Ditha Aulya Afanty (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Marital conflict affects the social, psychological, and spiritual stability of family life, yet Qur'anic values are often discussed separately from practical conflict-resolution processes. This study analyzes patience and steadfast faith in addressing marital conflict through thematic exegesis of Qur'anic verses on life's trials. It employed a qualitative library research design using the maudhu‘i method. Primary data comprised verses concerning al-ibtilā’, patience, steadfast faith, gratitude, tawakkul, mediation, reconciliation, and marital decision-making. Secondary data were drawn from exegetical works and relevant scholarly literature. Data were collected through documentation and analyzed by classifying the verses, examining their contexts and interpretations, comparing sources, and synthesizing thematic meanings. The findings identify four interconnected themes: forms of life's trials, patience as an active response, steadfast faith and tawakkul as spiritual orientation, and the application of these values to marital conflict resolution. Patience is expressed through emotional regulation, perseverance, self-reflection, constructive communication, and prudent decision-making. Steadfast faith provides moral direction, responsibility, hope, and trust in Allah after appropriate effort. These values are operationalized through mediation by hakam, reconciliation (iṣlāḥ), and decisions to maintain marriage according to ma‘rūf or end it with iḥsān. The study concludes that patience and steadfast faith constitute an integrated Qur'anic framework for responding to marital conflict actively, justly, and responsibly while protecting the rights of both spouses.